If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + -1b = cx + -7 Reorder the terms: ax + -1b = -7 + cx Solving ax + -1b = -7 + cx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. ax + -1b + b = -7 + b + cx Combine like terms: -1b + b = 0 ax + 0 = -7 + b + cx ax = -7 + b + cx Divide each side by 'x'. a = -7x-1 + bx-1 + c Simplifying a = -7x-1 + bx-1 + c Reorder the terms: a = bx-1 + c + -7x-1
| 2b^2-9b+9= | | 7(x+5)=6(x-6)+x | | 3x-5=-6x+14 | | 3x-5=-6+14 | | 6y+9+9y= | | 9f+9f=2 | | 4.5(7.6z+3)-3= | | lnx+x=5 | | 5x^2+6x+13=0 | | 9y-11=-10x+5 | | 7.6(4.5z-3)+3= | | y+8=7x | | ln(m)=.5(ln(x^2-y)) | | x/2-29=22 | | -5(-3)(-7)(-1)= | | 7(x+3)+2=7x+9 | | 3x^2/3x | | 0.18(2x)=29.5 | | 8x+10y=170 | | 0.18(2x)=59 | | y-15x=3 | | -17.3-m=22.8 | | 5+30=x+6 | | 2xy+10=90 | | x^9=-7 | | 3x+39=0 | | 3i*3i= | | -0.9(7.5w-6)-9= | | i*3i= | | 9(x-4)+x=10(x-4)+4 | | .02=15.4 | | -5x+3.6=2.1-4x |